Spectral analysis of second order quantum difference operator over the sequence space lρ (1 < ρ < ∞) - Kalita, N.; Dutta, A.J. (Bulletin of the Karaganda University, 2025)
In this article, we study the spectrum, fine spectrum and boundedness property of second order quantum difference operator Δ2q (0 < q < 1) over the class of sequence lρ (1 < ρ < ∞), the pth summable sequence space. The second order quantum difference operator Δ2q is a lower triangular triple band matrix Δ2q (1-(1+ q), q). We also determine the approximate point spectrum, defect spectrum, compression spectrum, and Goldberg classification of the operator on the class of sequence. We obtained the results by solving an infinite system of linear equations and computing the inverse of a lower triangular infinite matrix. We also provide appropriate examples along with graphical representations where necessary
Keywords: spectrum; difference operator; infinite matrices; triple-band matrix